Differential phosphorus ábsorption by cacao varieties - Rosand, Percy Cabala; Mariano, Antonio H. (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was carried out in greenhouse, in a rnodified Hoagland solution (0.2 of the concentration), comparing the cacao cultivar crosses SIC 864 x SIC 328, SIC 823x ICS 1, SIC 831 x Sca 6, SIC 831 x IMC 67 and Catongo from open pollination, to determine which of them were the most efficient in nutrient absorption and in tolerance to soil acidity. A completely randomized design was used with three replications. Growth, leaf area, root development and P content at 0, 10, 20, 30, 40, 60 and 90 days from transplanting were measured. For total dry matter production and P content SIC 831 x Sca 6 was superior to the other cultivars, and also had both higher secondary root surface and length and also larger leaf area. An exponential equation for cultivar growth in relation to time was suitable for adjusting the experimental data and again SIC 831 x Sca 6, followed by SIC 831 x IM 67, were superior in all periods. 'Catongo' showed the worst performance. A high correlation between the dry matter content of the secondary roots and P absorption was found. It was concluded, therefore, that the extension of the root system strongly influenced the P absorption capacity of the five cultivars.